The effect of application of contextual teaching and learning (CTL) model-based on lesson study with mind mapping media to assess student learning outcomes on chemistry on colloid systems - Annisa Fadillah; Ni Putu Laksmi Cintya Dewi; Dimas Ridho; Ahmad Nurkholis Majid; Meidiana Nur Budi Prastiwi (International Journal of Science and Applied Science: Conference Series, 2017)
The research was conducted to determine the effect of the application of CTL learning model based on lesson study with mind mapping media to the learning outcomes of students on colloid systems. The population of this research was all students of grade XI of SMA N 1 Sunggal. The sample was taken using on the purposive random sampling. The Experiment class was taught with Contextual Teaching and Learning (CTL) model based on Lesson Study with Mind Mapping media and the control class taught with conventional learning model. The data was collected using an objective test was consisting of 20 questions which validity, reliability, level of difficulty and power of difference had been tested. T test results showed that tcalculate = 2.1 and ttable = 1.6697 thus tcalculate> ttable which means that Ha is accepted and Ho is rejected. The enhancement of the student learning outcomes showed that the results of experiment class are g = 72.88%, while the control class is 68.97%. From the percentage, it can be seen that learning outcomes of the experiment class are greater than the control class. The analysis of developing cognitive aspects pointed out that C1 = 70.02%, C2 = 73.58%, C3 = 68.63%, Thus the domain of cognitive level are on the cognitive aspects of C2. The result of Lesson Study Analysis showed the results of 71.09% at the first lesson and 88.28% at the second lesson. It means that there is increasing adherence to the indicators after two lessons. Based on the above results, it can be concluded that the result of studying chemistry of the students of class XI of SMA Negeri I Sunggal TA 2014/2015 taught by a CTL model based  on Lesson Study with Mind Mapping media was higher (72.88%) than those taught by conventional learning models (68.97%) in the subject matter of colloids System.